(untitled) (Scientific journal of the Fergana State University, 2023)
The article contains data about legendary horses of an ancient state of Fergana (Davan, Day-yuan) which played an important role in the history of Central Asia. The petroglyphs incised onto rocks in Aravon and Ayrimachtau studied by archeologists A.N.Bernshtam and Yu.A.Zadneprovsky and those petroglyphs’ historical importance have been discussed in the article. The recent discoveries of petroglyphs found near (Ulug’tog’) the archeological destination of Mingtepa (Ershi) [17] which was the capital of the ancient state of Fergana, their importance for the sciences of history and archeology, how important discoveries they are for the scientific study of the history of ancient state of Fergana was explained thoroughly in the article.